Operator Performance Analysis Using Overall Labor Effectiveness Method with Root Cause Analysis Approach - Pratiwi Rahmadiani; Elisa Kusrini (Asian Journal of Social and Humanities, 2023)
The growth of the manufacturing sector in Indonesia has slowed down due to the increase in COVID-19 cases, which has led to a decrease in the production volume of companies. This impact needs to be reassessed by each company, and one way to address it is by continuously improving company productivity. PT X is one of the companies in the manufacturing sector that has a program to continuously enhance its productivity, with its production result being pianos. This study focuses on the performance of operators in a specific production area that has consistently not met the company's productivity target over a period. The objective is to determine the effectiveness of the operators in that area using the Overall Labor Effectiveness (OLE) method. Subsequently, the obtained OLE results will be analyzed using the Root Cause Analysis (RCA) method, and improvement proposals will be provided, supported by the House of Quality (HOQ) method and previous literature. The research results indicate issues in one of the OLE variables, namely the performance ratio. Root cause analysis was conducted to identify the underlying issues, assisted by brainstorming tools, the 5-why method, and a fishbone diagram. This analysis revealed three main problems. Furthermore, two design proposals were formulated using the HOQ framework, and an additional proposal was based on previous research findings.